СИФАТЛИ ТАЪЛИМ БЕРИШДА ТАЛАБАЛАРНИНГ КОММУНИКАТИВ КОМПЕТЕНЦИЯСИНИ РИВОЖЛАНТИРИШ - Абдиев, Б.Т. (SCIENCE and SOCIETY, 2023)
This article is analyzed modern methods, didactic materials and the activities of the teacher in providing quality education from the framework of modern pedagogical science. The place and role of students' has been widely analyzed communicative competence in quality education.
Keywords: reform; education; system; competence; development; technology; convention; didactics; creative; model; methodology; e-learning; student; subject; humanitarian; communicative